Neurotoxins and Fillers for Skin Rejuvenation - Mayor, Jessica; Grunebaum, Lisa (Facial Plastic Surgery, 2014)
The ephemeral effects of neurotoxins and fillers are well described for facial remodeling and rejuvenation. Less is known about their long-term effects on skin rejuvenation and neocollagenesis. This article aims to review current available science and literature to support the use of these cosmetic procedures as lasting antiaging treatments.
Keywords: fillers; neurotoxins; rejuvenation; antiaging